Project management analysis for strengthening the Pancasila student profile at State Junior High School 19 Ambon - Pattiasina, Andito; Papilaja, J; Lekatompessy, J. E (Asatiza: Jurnal Pendidikan, 2024)
of the Merdeka curriculum, aimed at cultivating students in Indonesia to embody and practice the core values of Pancasila in their everyday lives as citizens. This study aims to analyze the project management involved in the implementation of the Pancasila Student Profile at State Junior High School 19 Ambon. The research adopts a qualitative approach, employing data collection methods such as interviews, observations, and document analysis. The respondents include the principal, vice principal for curriculum, project supervisor, project leader, project treasurer, three students, and two parents of Grade 8 students. Data were analyzed using stages of data collection, reduction, display, and conclusion drawing. The findings of this research highlight the necessity of effective project management in ensuring that the Pancasila Student Profile program is executed in accordance with regulations and contributes to meaningful changes within the school. The study recommends that the principal maintain strong communication with the project supervisor prior to implementing the plan and foster a commitment to enhancing teachers' competencies in delivering the Pancasila Student Profile program. This will ensure better outcomes for students at State Junior High School 19 Ambon.